Review of diagnostic methods for prostate cancer with consideration of MRI-TRUS fusion biopsy - Sebastian Bąk; Kamil Budzeń; Paweł Wesołowski; Tomasz Stachura; Konrad Gładysz (Kazimierz Wielki University, 2022)
Introduction and purpose of the study: Prostate cancer is one of the most common malignancies in the human population worldwide. The continuous development of imaging methods allows for its increased recognition. Conclusions have been drawn that MRI-TRUS (magnetic resonance imaging - transrectal ultrasonography) fusion biopsy is superior to other diagnostic methods. The aim of this study is to review the available studies and publications and determine which method of diagnosing prostate cancer is most effective. Materials and Evidence: We reviewed the literature available on PubMed and Google Scholar using the words "fusion biopsy"; "prostate diagnosis"; "prostate cancer"; "transrectal ultrasonography". Results: The diagnosis of prostate cancer is made possible by a range of tests such as transrectal palpation, measurement of prostate specific antigen, transrectal ultrasonography, needle biopsy and MRI. The combination of biopsy, MRI and transrectal ultrasonography has led to the development of fusion biopsy. It combines the high-resolution features of MRI and the real-time images provided by ultrasound. Conclusions: The higher cost of the test and the need for specialised equipment together with the advanced software required for fusion biopsy ultimately provides a statistically significant higher success rate for the diagnosis of prostate cancer. Mentioned the effects of this method, further development and dissemination is expected.